2016
DOI: 10.1093/ndt/gfv436
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of HIV-associated immune complex kidney disease

Abstract: These findings suggest a pathogenic role for HIV replication in the development of HIVICK and that ART may improve kidney function in patients who have detectable HIV RNA at the time of HIVICK diagnosis. Our data also suggest that IgA nephropathy should be viewed as a separate entity and not included in the HIVICK spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 20 publications
0
79
0
1
Order By: Relevance
“…The patients receiving cART over a 3-year period showed stabilization in eGFR and an improvement in proteinuria, but these findings were not statistically significant. Booth et al 46 recently reported an observed significant reduction in proteinuria and improvement in eGFR in patients with HIVICD initiated on cART.…”
Section: Antiretroviral Therapymentioning
confidence: 96%
See 1 more Smart Citation
“…The patients receiving cART over a 3-year period showed stabilization in eGFR and an improvement in proteinuria, but these findings were not statistically significant. Booth et al 46 recently reported an observed significant reduction in proteinuria and improvement in eGFR in patients with HIVICD initiated on cART.…”
Section: Antiretroviral Therapymentioning
confidence: 96%
“…18,34,35 HIVICD has not been extensively studied, and the direct role of HIV infection in its pathogenesis is not known. 44,45 Booth et al 46 recently reported on a multicentre study describing the clinical characteristics and outcomes of HIVICD in renal biopsies between 1998 and 2012. Of 265 biopsies, 92 revealed immune complex disease (ICD).…”
Section: Spectrum Of Hiv-associated Ckdmentioning
confidence: 99%
“…HIVICK is associated with immune complex formation and renal deposition attributable to the presence of viral antigens and polyclonal immunoglobulin expansion associated with recurrent infections in these patients . Immunoglobulin A (IgA) nephropathy, post‐infectious glomerulonephritis, lupus‐like glomerulonephritis, cryoglobulinemia and membranoproliferative glomerulonephritis are the most frequent immune complex‐mediated glomerulonephritis in HIV‐infected patients .…”
Section: Pathogenesismentioning
confidence: 99%
“…HIVAN and HIV immune complex disease of the kidney (HIVICK) are the most common HIV-related nephropathies, resulting from the exposure of renal cells of a genetically susceptible host to viral antigens [82]. HIVAN results from direct cytotoxicity leading to podocyte proliferation and dedifferentiation, apoptosis of tubular epithelial cells and tubulointerstitial inflammation [82,83] HIVICK is associated with immune complex formation and renal deposition attributable to the presence of viral antigens and polyclonal immunoglobulin expansion associated with recurrent infections in these patients [84]. Immunoglobulin A (IgA) nephropathy, post-infectious glomerulonephritis, lupus-like glomerulonephritis, cryoglobulinemia and membranoproliferative glomerulonephritis are the most frequent immune complexmediated glomerulonephritis in HIV-infected patients [84].…”
Section: Pathogenesismentioning
confidence: 99%
“…Compared with HIVAN, HIVICK patients have more antiretroviral therapy exposure, lower viral loads, and higher CD4 and eGFR [10, 15, 18, 19]. Indeed, HIVICK is far less likely to progress to ESRD than HIVAN [15].…”
Section: Introductionmentioning
confidence: 99%